Pathology of cardio-pulmonary disorders in canines - Pradeep M (Centre of Excellence in Pathology, College of Veterinary and Animal Sciences, 2003)
The present study was undertaken to assess the prevalence and pathology of various cardiac and pulmonary disorders in dogs. The data collected from the autopsy records maintained at the Centre of Excellence in Pathology, Mannuthy and seventy eight samples of heart and lungs from necropsy cases formed the basis of the study. Ninety nine per cent cases showed varying types of cardiac and pulmonary lesions. The highest incidence in the heart was dilated (75.32 per cent) and hypertrophic (15.58 per cent) cardiomyopathies. The other lesions found were hydropericardium, cardiac tamponade, haemorrhage, myocarditis, endocarditis, endocardial fibroelastosis, valvular blood cyst coronary arteriosclerosis and mural. thrombus. Myocardial infarction was found to be confined to the left ventricles and interventricular septum in all the encountered cases (5.19 per cent). Pulmonary congestion (70.51 per cent), haemorrhage (32.47 per cent) and edema (31.17 per cent) were observed with higher incidence rate. The other lesions found in the lungs were bronchitis, emphysema, pneumonia, collapse, infarction, mineralization, ossification, anthracosis and endarteritis obliterans. Metastatic osteosarcoma in the lungs, metastatic lymphosarcoma in the heart and lungs were also observed. The incidence of cardio-pulmonary disorders encountered was relatively high. The need and scope for investigation into the pathological disorders of the heart and lungs of canines were highlighted.